COGNITIVE-ENHANCING PROPERTIES OF MORINDA LUCIDA (RUBIACEAE) AND PELTOPHORUM PTEROCARPUM (FABACEAE) IN SCOPOLAMINE-INDUCED AMNESIC MICE - Taiwo O, Elufioye; Halimah A., Hameed (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Cognitive disorders associated with aging have been successfully managed by African traditional medical practitioners using various plants. This study evaluated the cognitive enhancing potentials of Morinda lucida (L) Rubiaceae and Peltophorum pterocarpum (DC) ex. K Heyne in scopolamine induced amnesic animals. Materials and Methods: The anti-amnesic activity of the ethyl acetate extracts of Morinda lucida and Peltophorum pterocarpum at doses of 4 mg/kg, 6 mg/kg and 8 mg/kg were assessed in scopolamine induced amnesic mice using Morris water maze test model. Effect of the extracts on the histology of the hippocampus was also evaluated. Results: The ethyl acetate extract of Morinda lucida and Peltophorum pterocarpum ameliorated scopolamine induced memory deficit in the animals under study. There was no effect of the extract on the histology of the hippocampus. However, there was an increase in the density of cells in the hippocampus of treated group as compared to the untreated. Conclusion: Morinda lucida and Peltophorum pterocarpum showed considerable enhancement of cognition in scopolamine induced amnesic mice.